Uji Kualitatif Kandungan Methanyl Yellow Pada Manisan Buah Yang Beredar di Mamuju - Tunmunawwarah, Isna; Tikirik, Wita Oileri; Nur, Akbar; Tarnoto, Tenny (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Methanyl yellow is a synthetic dye, in the form of a brownish yellow powder, soluble in water, and slightly soluble in acetone which contains aromatic azo chemical compounds which have N=N bonds which can accumulate in the human body and are carcinogenic if consumed in the long term can cause abnormalities in human organs that cause tumors in various tissues of the liver, bladder, digestive tract or skin tissue. This research is a qualitative descriptive study with esting in the laboratory using a test kit to determine whether or not there is methanyl yellow content in candied fruit circulating in Mamuju. The results of this research show that 7 samples of candied fruit circulating in Mamuju have been subjected to organoleptic and chemical tests, so they were declared not to contain methanyl yellow. However, it is still recommended that people be more selective in choosing the food they want to consume. This research can be continued using UV Vis spectrophotometry so that the research is more accurate by knowing the level of methanyl yellow content in certain samples